JEAN-PAUL SARTRE FELSEFESİNDE KENDİSt-İÇÎN-VARLIfCJN ONTOLOJÎK ANALİZİ - Talip Karakaya (Felsefe Dünyası)
Consciousness, which is discussed more and more as a result of Edmund Husserl's phenomenological studies in particular, is seen to be making contemporary intellectuals busy. Consciousness expressed by the concepts of cognition, sense, perception, etc. ca- , use disputes among both idealist and materialist thinkers. It also occupies an important place in Jean-Paul Sartre's ontology. Is consciousness, which is considered by representatives of all extreme poles of philosophy, a phenomenon particular to human beings only? If so, does it contain only subject or object? What is its origin or core? Why does Sartre give an importance place to this in his philosophy? This work aims to provide an analysis and answers to these questions.. Parallel to this, in most of materialists, consciousness is a reflection of the matter and social origin developed to the highest level in animate beings, whereas in Husserl it is the consciousness of something. In Sartre, this concept has a rather different meaning. For him, no ego can create consciousness, and it belongs to being and is born with it. Consciousness, which is a result of the struggle for existence, tries to be full of itself and be fundamental to its existence. So, it has to befor-itself-in-itself, for it inquires into what is expected from itself, realises its full being and gets rid of the state of being nonsense. In short, according to Sartre, the characteristic of being-for-itself is not limited to consciousness. In this work, I tried to consider how being-for-itself struggles for its being, the connection of being-for-itself with non-existence, its the struggle to be free. I also deal with the probabilities it has and its place in the concept of time from Sartre's ontological and existentialist viewpoint.